El grabado del Cándalo, Garciaz (Cáceres) - Rubio Andrada, Manuel; Pastor González, Vicente (Zephyrvs, 2009)
RESUMEN: Se presenta un nuevo grabado de la época del Bronce en el término de Garciaz, Cáceres. Grabados semejantes se conocían sobre todo en la comarca de Hurdes y norte de Portugal. De su estudio se deduce una relación armamentista con el mundo astral. ABSTRACT: A new engraving from Bronze age, has been found in Garciaz boundary (Cáceres). Similar engraving were already known in "Las Hurdes" district and in Portugal (norther áreas). It has been deduced from its research a relation between the arms woeld and the cosmisc one.